Markers of pediatric respiratory distress predictive of poor outcome in low- and middle-income countries: a systematic review - Anna B Hedstrom; Amelie O von Saint Andre-von Arnim; Kalee L Grassia; Katie R Nielsen (Inishmore Laser Scientific Publishing Ltd, 2020)
# Background Lower respiratory tract diseases remain significant causes of pediatric mortality in low- and middle-income countries. In these settings, staff must quickly triage patients for timely initiation of treatment and potential transfer to higher levels of care. World Health Organization (WHO) guidelines focus on two physical exam findings - tachypnea and chest indrawing - without addressing the multitude of other respiratory assessment tools used by healthcare workers. This lack of additional validated markers makes triage of patients challenging. The aim of this study was to systematically review respiratory assessments in children under five years of age that have been associated with poor clinical outcomes in resource limited settings. # Methods We conducted a systematic search for studies published between January 1, 2008 and January 21, 2018 using Ovid MEDLINE and Embase including patients five years of age and younger. Major categories of search terms were "respiratory distress", "respiratory symptoms", "low- and middle-income countries" and "clinical assessment". We extracted data relevant to study characteristics, respiratory assessments and clinical outcomes. # Findings Out of 2317 identified publications, 63 full text articles fit inclusion criteria, 56 reported statistically significant associations and were included in analyses and these publications included 53 unique study populations. Publications were from: low-income countries (26%), lower middle-income countries (55%) and upper middle-income countries (19%). The most common respiratory assessments were hypoxia (50%), tachypnea (46%) and chest indrawing/retractions (38%). Death was the most frequently reported clinical outcome (54%), followed by hypoxia (23%). Hypoxia, chest indrawing/retractions and tachypnea were the most commonly reported risk factors for mortality. # Conclusions Hypoxia, chest retractions and tachypnea are key risk factors for mortality form pediatric respiratory disease in resource limited settings. Death is the primary outcome of interest for research in this area. As pediatric respiratory interventions are deployed in these settings, better understanding of which respiratory assessments are predictive of poor clinical outcomes could guide management and transfer of care decisions.